2018
DOI: 10.1111/1462-2920.14297
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial interactions during sequential degradation of cyanobacterial necromass in a sulfidic arctic marine sediment

Abstract: SummarySeafloor microorganisms impact global carbon cycling by mineralizing vast quantities of organic matter (OM) from pelagic primary production, which is predicted to increase in the Arctic because of diminishing sea ice cover. We studied microbial interspecies‐carbon‐flow during anaerobic OM degradation in arctic marine sediment using stable isotope probing. We supplemented sediment incubations with 13C‐labeled cyanobacterial necromass (spirulina), mimicking fresh OM input, or acetate, an important OM degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 89 publications
7
46
0
Order By: Relevance
“…Our approach, however, indicated that the Desulfobulbaceae displayed even higher assimilation rates than the Desulfobacteraceae both in whole core and in slurry experiments. Among the Desulfobacteraceae the Sva0081-MBG assimilated acetate in higher rates than the average Desulfobacteraceae population (Figure 3), while in arctic sediment, this group was reported to assimilate only small amounts of acetate into biomass (Müller et al, 2018). Interestingly, the Sva0081-MBG is consistently found in high cell abundances in Wadden Sea sediments (up to 8% of total cell counts, Ovanesov, 2012) and has been frequently detected in various types of marine sediments worldwide (Wang et al, 2013; Liu et al, 2014; Zheng et al, 2014; Dyksma et al, 2017; Probandt et al, 2017; Müller et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach, however, indicated that the Desulfobulbaceae displayed even higher assimilation rates than the Desulfobacteraceae both in whole core and in slurry experiments. Among the Desulfobacteraceae the Sva0081-MBG assimilated acetate in higher rates than the average Desulfobacteraceae population (Figure 3), while in arctic sediment, this group was reported to assimilate only small amounts of acetate into biomass (Müller et al, 2018). Interestingly, the Sva0081-MBG is consistently found in high cell abundances in Wadden Sea sediments (up to 8% of total cell counts, Ovanesov, 2012) and has been frequently detected in various types of marine sediments worldwide (Wang et al, 2013; Liu et al, 2014; Zheng et al, 2014; Dyksma et al, 2017; Probandt et al, 2017; Müller et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…7B), suggests that they were also important degraders of the added lignocellulose extract under anoxic conditions. The role of sulfate reducing bacteria (SRB) in organic matter remineralization marine sediments is well known (Jørgensen, 1982), and proceeds often through the utilization of low molecular weight volatile fatty acids (Muller et al, 2018). Thus, the increased growth of SRB in the samples that received lignocellulose is likely due to their utilization of low molecular weight volatiles produced during the degradation of the lignocellulose by the greater microbial community.…”
Section: Most Abundant Groups In Lc+ At 2 Weeksmentioning
confidence: 99%
“…The microbial degradation of organic macromolecules in anoxic marine sediments is a complex inter-species process involving "primary degraders" that break down larger macromolecules into oligomers and monomers for fermentation to alcohols, lactate, and/or short-chain volatile fatty acids (VFAs), which are then mineralized to CH 4 , CO 2 and/or H 2 [21]. "Terminal oxidizers" of fermentation products prevalent in marine sediments, such as sulfatereducing microorganisms (SRM), have been relatively well studied [22][23][24][25][26][27]. On the other hand, the key microbial players responsible for the primary hydrolysis of different types of organic matter and macromolecules are poorly understood.…”
Section: Introductionmentioning
confidence: 99%